PERSEPSI DEALER MOBIL TERHADAP KEBIJAKAN INSENTIF PAJAK MOBIL HYBRID (Studi Kasus Pada Honda Sukun Malang) - Andy Setiawan; Iwan Triyuwono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research is aimed to determined how car dealer’s perception from Honda Sukun Malang regarding tax incentives on hybrid cars. This research uses qualitative research with case study method. Information from this research was obtained from interviews with Honda Sukun’s employees and also from any sources such as journals, newsletters, magazines, and etc. that is considered relevant and supporting to the research. The results showed that CRZ as a hybrid car from Honda is more expensive when compared to the other cars due to the imposition of various taxes. The expensive price make the condition of CRZ sales become the most worse sales when compared to the other car sales, despite that CRZ is an environmentally friendly hybrid car with fuel-efficient. The provision of tax incentives by the government against CRZ is a way out that can be taken by the government to deliver CRZ widely in the market. With incentives, the price will be cheaper so that can be accepted more by society. As well as tax incentives from the government for car Low Cost Green Car, CRZ was also entitled to receive the same tax incentives. Various problems such as the issue of local content and the production sites of CRZ makes the tax incentives for hybrid cars is never given by the government. Meanwhile, the government is confuse to limit the fuel consumption that is continues to increase each year as a result of the growth of the vehicles in Indonesia.Keywords : Car, Hybrid, Incentive, Tax, Honda CRZ.